Ukraińsko-rosyjski konflikt na wschodzie Ukrainy a propaganda w mediach rosyjskich - Yuskiv, Bohdan M.; Khomych, Serhii; Юськів, Богдан Миколайович; Хомич, Сергій (Państwowa Wyższa Szkoła Zawodowa im. Jana Grodka w Sanoku, 2017)
Ukrainian–Russian conflict on the east of Ukraine and Russian media propaganda The subject of this research is one of the most pressing problems of today’s Ukraine – military conflict with Russia, also known as “hybrid war”.Among the specific features of this war is the usage of non-military, especially propaganda means along with the military ones.The aim of the research was to analyze possible connections between the Russian backed separatist forces, as well as Russian special operation forces on Ukrainian East, and the Russian media propaganda. It was proved that separatists’ activities are more influenced by Russian propaganda, than by international activities aimed at peaceful resolving of the conflict. As a result, the reversed regression model was created, which can prove direct connection between the number of firefights and specific propaganda phrases used by Russian “RT” propaganda channel. The model can be used to predict occurrence and the number of firefights by analyzing the propaganda content according to the key words.
Ukrainian–Russian conflict on the east of Ukraine and Russian media propaganda